Iranian Case of N-acetyl-glutamate Synthase (NAGS) Deficiency Treated with N-carbamylglutamate: A Novel Approach - Sayarifard F; Hadipour F; Hadipour Z; Häberle J; Shafeghati Y; Sagheb S; Sarkhail P (Medical Research and Its Applications Vol. 2, 2024)
Aim: The present study describes the first Iranian case of NAGS deficiency that presented with severe neonatal hyperammonemia in the first week of his life. This case report highlights the pan-ethnic nature of NAGS deficiency and the importance of starting treatment early to prevent severe neurological diseases. Background: N-acetyl-glutamate synthase (NAGS) deficiency is a rare cause of severe neonatal hyperammonemia. Case report: An 8-day-old boy, who was born of non-consanguineous Iranian parents by cesarean section, was admitted to the neonatal intensive care unit due to poor feeding, unconsciousness, and seizures. High Ammonia (920 \(μ\)mol/L, ref. < 100), high plasma glutamine (1628.6 \(μ\)mol/L, ref. 410-960) and alanine (1151.5 \(μ\)mol/L, ref. 200-600), low plasma citrulline (6.6 \(μ\)mol/L, ref. 8-47) and arginine (26.7 \(μ\)mol/L, ref. 20-160), without orotic aciduria (orotic acid in urine below detection limit) was revealed in the metabolic work-up. Based on these results, carbamoyl-phosphate synthetase 1 (CPS1) or NAGS deficiency was suspected. The infant was treated with peritoneal dialysis, intravenous sodium benzoate, L-arginine, and oral sodium phenylbutyrate and ammonia declined to 390 \(μ\)mol/L after 10 days Discussion: The genetic analysis of the patient and parents confirmed the NAGS deficiency with a novel heterozygous maternal missense mutation in exon 5 c. 1172T>G (p. Leu391Arg) and the known change in exon 6c.1450T>C (p. Trp484Arg) on the paternal allele. The use of carglumic acid (Carbaglu®, Orphan Europe Recordati, Paris, France) started at 3 months and lasted for 1.5 months. The ammonia level declined to normal (55 \(μ\)mol/l) after 24 hours, for the first time in the patient. The decision to discontinue carglumic acid treatment (while sodium benzoate and sodium phenylbutyrate were continued) was made in consultation with the patient’s parents due to the severe neurological impairment caused by the initial hyperammonemic crisis and the challenges of obtaining the drug in Iran. The patient passed away five days later from hyperammonemic decompensation. Conclusion: Despite being rare, NAGS deficiency seems to be a pan-ethnic condition. Thus, in the case of hyperammonemia without orotic aciduria but with low plasma citrulline, NAGS deficiency should be considered and a trial with carglumic acid should be started as early as possible. Our case highlights the importance of early recognition and treatment in the prognosis of neonatal onset NAGS deficiency. The innovative approach to treatment and care optimization holds great promise for improving outcomes among hyperammonemic patients, particularly those afflicted with NAGS deficiency.